Penguatan Kapasitas Koperasi Merah Putih Sebagai Penggerak Ekonomi Lokal Berbasis Pertanian di Desa Cikidang, Lembang - Nanda Ravenska; Reni Wijayanti; Adhika Bergi Nugroho; Siti Annisa Fauziah Pasha (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The Red-and-White Cooperative (Koperasi Merah Putih or KMP) is expected to strengthen rural economies through the collective management of local resources. This community service activity aimed to strengthen the capacity of KMP as a driver of local agricultural-based economic development in Cikidang Village, Lembang District, West Bandung Regency. The program employed educational and participatory approaches, including counseling, training, interactive discussions, and simple practical sessions. The topic covered cooperative strengthening, value-added agricultural development, and the utilization of organic waste as fertilizer. The result indicated improved participant understanding of the strategic role of cooperatives in supporting local economic development. Participants also gained insights into agricultural business opportunities and organic waste management practices that can support sustainable agriculture. These findings suggest that strengthening the capacity of KMP can contribute to promoting a more independent and sustainable local economy.